2023
DOI: 10.1371/journal.pntd.0011252
|View full text |Cite
|
Sign up to set email alerts
|

The Pampa del Indio project: District-wide quasi-elimination of Triatoma infestans after a 9-year intervention program in the Argentine Chaco

Abstract: Background The elimination of Triatoma infestans, the main domestic vector of Trypanosoma cruzi, is lagging behind expectations in the Gran Chaco region. We implemented an insecticide-based intervention program and assessed its long-term effects on house infestation and bug abundance in a resource-constrained municipality (Pampa del Indio, northeastern Argentina) inhabited by creole and the Qom indigenous people (2007–2016). Key questions were whether district-wide data integration revealed patterns concealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 99 publications
2
32
0
Order By: Relevance
“…These models identified two main regions with infestation risk not explained by the sociodemographic and environmental variables included in the fixed-effects models. The main region with the largest size and a positive risk of domestic infestation across both intervention periods occurred in Area I [ 22 ], where house infestation over the first 3 years postintervention was strongly associated with mud walls, thatched roofs, high refuge availability for triatomines, domestic host abundance and lack of domestic use of insecticides [ 25 ]. Area I displayed the highest prevalence of preintervention house infestation (41.4%) and required proportionally more house sprays with pyrethroid insecticide than the rest of the municipality [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These models identified two main regions with infestation risk not explained by the sociodemographic and environmental variables included in the fixed-effects models. The main region with the largest size and a positive risk of domestic infestation across both intervention periods occurred in Area I [ 22 ], where house infestation over the first 3 years postintervention was strongly associated with mud walls, thatched roofs, high refuge availability for triatomines, domestic host abundance and lack of domestic use of insecticides [ 25 ]. Area I displayed the highest prevalence of preintervention house infestation (41.4%) and required proportionally more house sprays with pyrethroid insecticide than the rest of the municipality [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The municipality extends over approximately 60 km by 30 km and includes two loosely connected urban centers (Pampa del Indio and Pueblo Viejo), a peri-urban section (Parque Industrial) and 32 dispersed rural settlements. The rural section of the municipality was divided into four areas (I, II, II and IV) for operational purposes [ 22 ]. Based on a supervised classification, Rodríguez-Planes [ 30 ] showed that in Pampa del Indio the estimated percentage of land covered by different types of forests (with different degrees of degradation) was 74.4% and 72.4% in December 2006 and August 2015, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have identified risk factors of human infection with T. cruzi at different levels: individual, household, social group or community, and landscape or region [ 23 31 ]. In general, duration of exposure, the presence and abundance of infected triatomines in domiciles, building materials of walls and roof, and presence and number of infected dogs and cats and of other infected human residents in the household (i.e.…”
Section: Introductionmentioning
confidence: 99%